(untitled) (ModaPalavra e-periódico, 2021)
The article aims to present and analyze the stretch test method of Penélope Watkins, as well as to investigate the calculating method of pattern reduction for knitted garments. For this, two types of knit were used: one with 84% polyamide and 16% elastane and the other with 92% polyester and 8% elastane. As a result, two collants were made which were too tightly adjusted to the body, as the sample width of the stretch test was very narrow. Therefore, the authors of this article proposed a new sample width and two new collants were remade, following Watkins’ guidelines. The results showed a more adequate distortion of the knitted fabrics in the manufactured pieces.